Project-Based Teaching Materials in Increasing the Knowledge and Skills of Vocational High School Students - Muslim; Jalinus, Nizwardi; Ridwan; Sugiarto, Toto; Fernandez, Donny; Setiawan, Dedi (Mimbar Ilmu, 2023)
Many students graduate with inadequate knowledge and skills, so more effective learning methods are needed. So that student competency can increase, project-based learning modules must be developed. This study aims to measure the effectiveness of project-based teaching materials on light vehicle engine maintenance. The type of research used is experimental research with a quantitative approach. The subjects in this research were 30 students used to test the effectiveness of the teaching materials developed. Trials are collected to collect quantitative data in the form of learning outcomes tests and skills tests to obtain product effectiveness scores. The data analysis technique uses a one-shot case study regarding the classical completeness of the value of knowledge and skills learning outcomes. The research results show that the use of project-based teaching materials is effective. This is based on increased students' knowledge and skills after using these teaching materials. In conclusion, the effectiveness test in developing teaching materials for light vehicle engine maintenance used by students can increase knowledge and skills in the learning process. This can help students practically understand the concept of light vehicle engine maintenance and integrate it with previously learned knowledge.